Miguel Delibes' Parábola del náufrago: Utopia Redreamed - H. L. Boudreau (Studies in 20th & 21st Century Literature, 1976)
Delibes' anti-utopian novel is analyzed from a triple perspective: its internal exegesis, the author's literary development, and the three-phase Utopian genre. Artistic versus thematic orientation is examined via parabolic technique, linguistic characterization, and Parábola's internalization as its author's nightmare. The latter facilitates novelistic exposition through the control and order inherent in the associative language and logic of the dream. Delibes frees his Utopian world from the perquisites of reality by creating an estetic dimension and psychological verisimilitude uncommon in the genre.
Keywords: anti-utopian novel; Miguel Delibes; Utopia; Utopian genre; parabolic technique; artistic orientation; thematic orientation; Parábola del náufrago; Utopia Redreamed